Pilgrimage Satisfaction Of Religious Event-Nanda Devi Raj Jaat 2014 Uttarakhand (PUSA Journal of Hospitality and Applied Sciences, 2016)
Background: Pilgrimage to sacred place as an act of religious devotion is an age old tradition,  followed by religions all over the world and especially in India. Pilgrim satisfaction of religious  events indicates the quality of services rendered by the event organizers, prevents negative  evaluation and unfavourable word of mouth of the events. Considering a need for understanding  the pilgrim satisfaction of a religious event, a study was organized. Objective: The objective of  the study include measuring pilgrim satisfaction & identifying key factors that influence pilgrim  satisfaction and to know their relative importance. Method: Nanda Raj Jaat Uttarakhand 2014  was taken as case study for this paper. About 200 pilgrims who visited event were interviewed as a  sample with a structured questionnaire. Results: Results indicate that providing basic facilities to  the pilgrims would be single most important factor influencing the satisfaction. Conclusion: The  study concluded that arrangements at the event Nanda Raj Jaat 2014 have met the expectations  of the pilgrims moderately.
Keywords: Tourism; Religious event; Pilgrim Satisfaction; Nanda Devi Raj